Analysis of Democratic Parenting Styles Related to CRE Learning Motivation in High School Students - Agung Pratama Sitompul; Pujiati Pujiati; Hari Santoso (Jurnal Pendidikan Agama Kristen (JUPAK), 2025)
This study aims to analyze the relationship between democratic parenting and Christian Religious Education (CRE) learning motivation in high school students, which is motivated by low learning motivation and suboptimal family support in fostering spiritual learning enthusiasm. Using a descriptive qualitative method with a literature study approach, this study examines various relevant literature to understand the relationship between parenting styles and learning motivation. The results show that democratic parenting styles that balance affection, discipline, and open communication play an important role in building students' intrinsic and spiritual motivation. In the context of CRE, this parenting style creates a learning environment conducive to the growth of faith, responsibility, and Christian character. This study contributes theoretically to Christian education studies and offers practical guidance for parents and CRE teachers in shaping a generation that is steadfast in faith and highly motivated.